Keterkaitan Karakter Religius dengan Capaian Akademik Pendidikan Agama Islam pada Siswa Madrasah Tsanawiyah - Mu’taza Fiddini; Poppy Rachman; Ramdan Wagianto (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze students' religious character and examine its relationship with the academic value of Islamic Religious Education (PAI) at Madrasah Tsanawiyah Al Islamiyah Krejengan Probolinggo. This study is motivated by the importance of understanding how PAI academic values are not only cognitive achievements, but also as part of the process of forming students' religious character, especially in the context of Islamic boarding schools (pesantren) that have a strong religious environment and structured religious habits. This study uses a qualitative approach. Data collection techniques are carried out through observation, interviews with teachers, and documentation in the form of student grades. Data are analyzed th rough the stages of data reduction, data presentation, and drawing conclusions. Data processing of academic grades is done by calculating the average of students' PAI scores covering the subjects of Aqidah Akhlak, Fiqh, SKI, and Qur'an Hadith to obtain an overview of students' cognitive achievements. The results of the study indicate that students' religious character is generally in the good category as demonstrated by consistent religious activities. Students' PAI academic scores are also in the good category with a score range of 78–85. The relationship between academic values and religious character shows a mutually supportive relationship, where good religious understanding tends to be followed by religious practices that are reflected in students' daily behavior